Current-induced dynamics in carbon atomic contacts - Lü, Jing-Tao; Gunst, Tue; Hedegård, Per; Brandbyge, Mads (Beilstein Journal of Nanotechnology, 2011)
Background: The effect of electric current on the motion of atoms still poses many questions, and several mechanisms are at play. Recently there has been focus on the importance of the current-induced nonconservative forces (NC) and Berry-phase derived forces (BP) with respect to the stability of molecular-scale contacts. Systems based on molecules bridging electrically gated graphene electrodes may offer an interesting test-bed for these effects.Results: We employ a semi-classical Langevin approach in combination with DFT calculations to study the current-induced vibrational dynamics of an atomic carbon chain connecting electrically gated graphene electrodes. This illustrates how the device stability can be predicted solely from the modes obtained from the Langevin equation, including the current-induced forces. We point out that the gate offers control of the current, independent of the bias voltage, which can be used to explore current-induced vibrational instabilities due the NC/BP forces. Furthermore, using tight-binding and the Brenner potential we illustrate how Langevin-type molecular-dynamics calculations including the Joule heating effect for the carbon-chain systems can be performed. Molecular dynamics including current-induced forces enables an energy redistribution mechanism among the modes, mediated by anharmonic interactions, which is found to be vital in the description of the electrical heating.Conclusion: We have developed a semiclassical Langevin equation approach that can be used to explore current-induced dynamics and instabilities. We find instabilities at experimentally relevant bias and gate voltages for the carbon-chain system.
Keywords: carbon-nanoelectronics; current-induced forces; molecular contacts; nanoscale Joule heating; semiclassical Langevin equation

(untitled) - Tao, N. J. (Nat. Nanotechnol., 2006)

(untitled) - Moth-Poulsen, K.; Bjørnholm, T. (Nat. Nanotechnol., 2009)

(untitled) - Song, H.; Kim, Y.; Jang, Y. H.; Jeong, H.; Reed, M. A.; Lee, T. (Nature, 2009)

Curren-driven phenomena in nanoelectronics - Seideman, T. (Pan Stanford Publishing, 2011)

(untitled) - Dundas, D.; McEniry, E. J.; Todorov, T. N. (Nat. Nanotechnol., 2009)

(untitled) - Lü, J. T.; Brandbyge, M.; Hedegård, P. (Nano Lett., 2010)

(untitled) - Bode, N.; Kusminskiy, S. V.; Egger, R.; von Oppen, F. (Phys. Rev. Lett., 2011)

(untitled) - Lü, J. T.; Hedegård, P.; Brandbyge, M. (Phys. Rev. Lett., 2011)

(untitled) - Kubatkin, S.; Danilov, A.; Hjort, M.; Cornil, J.; Brédas, J.; Stuhr-Hansen, N.; Hedegård, P.; Bjørnholm, T. (Nature, 2003)

(untitled) - Geim, A. K.; Novoselov, K. S. (Nat. Mater., 2007)

(untitled) - Castro Neto, A. H.; Guinea, F.; Peres, N. M. R.; Novoselov, K. S.; Geim, A. K. (Rev. Mod. Phys., 2009)

(untitled) - Geim, A. K. (Science, 2009)

(untitled) - Meyer, J. C.; Girit, C. O.; Crommie, M. F.; Zettl, A. (Nature, 2008)

(untitled) - Jia, X.; Hofmann, M.; Meunier, V.; Sumpter, B. G.; Campos-Delgado, J.; Romo-Herrera, J. M.; Son, H.; Hsieh, Y.-P.; Reina, A.; Kong, J.; Terrones, M.; Dresselhaus, M. S. (Science, 2009)

(untitled) - Engelund, M.; Fürst, J. A.; Jauho, A. P.; Brandbyge, M. (Phys. Rev. Lett., 2010)

(untitled) - Guo, X.; Gorodetsky, A. A.; Hone, J.; Barton, J. K.; Nuckolls, C. (Nat. Nanotechnol., 2008)

(untitled) - Jin, C.; Lan, H.; Peng, L.; Suenaga, K.; Iijima, S. (Phys. Rev. Lett., 2009)

(untitled) - Börrnert, F.; Börrnert, C.; Gorantla, S.; Liu, X.; Bachmatiuk, A.; Joswig, J.-O.; Wagner, F. R.; Schäffel, F.; Warner, J. H.; Schönfelder, R.; Rellinghaus, B.; Gemming, T.; et al. (Phys. Rev. B, 2010)

(untitled) - Hobi, E., Jr.; Pontes, R. B.; Fazzio, A.; da Silva, A. J. R. (Phys. Rev. B, 2010)

(untitled) - Erdogan, E.; Popov, I.; Rocha, C. G.; Cuniberti, G.; Roche, S.; Seifert, G. (Phys. Rev. B, 2011)

(untitled) - Lin, Z. Z.; Yu, W. F.; Wang, Y.; Ning, X. J. (EPL, 2011)

(untitled) - Chen, W.; Andreev, A. V.; Bertsch, G. F. (Phys. Rev. B, 2009)

(untitled) - Fürst, J. A.; Brandbyge, M.; Jauho, A.-P. (EPL, 2010)

(untitled) - Akdim, B.; Pachter, R. (ACS NANO, 2011)

(untitled) - Adelman, S.; Doll, J. (J. Chem. Phys., 1976)

(untitled) - Kantorovich, L. (Phys. Rev. B, 2008)

(untitled) - Kantorovich, L.; Rompotis, N. (Phys. Rev. B, 2008)

(untitled) - Wang, J.-S. (Phys. Rev. Lett., 2007)

(untitled) - Lü, J. T.; Wang, J.-S. (Phys. Rev. B, 2008)

(untitled) - Nourtier, A. (J. Phys. (Paris), 1977)

(untitled) - Head-Gordon, M.; Tully, J. C. (J. Chem. Phys., 1995)

(untitled) - Brandbyge, M.; Hedegård, P. (Phys. Rev. Lett., 1994)

(untitled) - Brandbyge, M.; Mozos, J. L.; Ordejón, P.; Taylor, J.; Stokbro, K. (Phys. Rev. B, 2002)

(untitled) - Frederiksen, T.; Paulsson, M.; Brandbyge, M.; Jauho, A.-P. (Phys. Rev. B, 2007)

(untitled) - Schmid, A. (J. Low Temp. Phys., 1982)

Quantum Kinetics in Transport and Optics of Semiconductors - Haug, H.; Jauho, A.-P. (Springer, 2008)

(untitled) - Bevan, K. H.; Guo, H.; Williams, E. D.; Zhang, Z. (Phys. Rev. B, 2010)

(untitled) - Brandbyge, M.; Stokbro, K.; Taylor, J.; Mozos, J. L.; Ordejón, P. (Phys. Rev. B, 2003)

(untitled) - Brandbyge, M. (Nat. Nanotechnol., 2009)

(untitled) - Brandbyge, M.; Kobayashi, N.; Tsukada, M. (Phys. Rev. B, 1999)

(untitled) - Rivelino, R.; dos Santos, R. B.; de Brito Mota, F.; Gueorguiev, G. K. (J. Phys. Chem. C, 2010)

(untitled) - Soler, J. M.; Artacho, E.; Gale, J. D.; Garcia, A.; Junquera, J.; Ordejón, P.; Sánchez-Portal, D. (J. Phys.: Condens. Matter, 2002)

(untitled) - Sergueev, N.; Roubtsov, D.; Guo, H. (Phys. Rev. Lett., 2005)

(untitled) - Brenner, D. W. (Phys. Rev. B, 1990)

Electronic Structure, the Properties of Solids: The Physics of the Chemical Bond - Harrison, W. A. (Dover Publications, 1989)

(untitled) - Guinea, F.; Katsnelson, M. I.; Geim, A. K. (Nat. Phys., 2010)

Computational Soft Matter: From Synthetic Polymers to Proteins - Allen, M. P. (Introduction to Molecular Dynamics Simulation, 2004)

(untitled) - Wang, J.-S.; Ni, X.; Jiang, J.-W. (Phys. Rev. B, 2009)

(untitled) - Ioffe, Z.; Shamai, T.; Ophir, A.; Noy, G.; Yutsis, I.; Kfir, K.; Cheshnovsky, O.; Selzer, Y. (Nat. Nanotechnol., 2008)

(untitled) - Ward, D. R.; Halas, N. J.; Ciszek, J. W.; Tour, J. M.; Wu, Y.; Nordlander, P.; Natelson, D. (Nano Lett., 2008)

(untitled) - Chae, D.-H.; Krauss, B.; von Klitzing, K.; Smeν, J. H. (Nano Lett., 2010)